Perancangan Tata Letak Gudang dengan Membandingkan Metode Dedicated Storage dan Class Based Storage (Studi Kasus: Perusahaan Komponen Otomotif) - Febriza Imansuri; Rahmat Dwi Febriyanto; Indra Rizki Pratama; Fredy Sumasto; Siti Aisyah (Fakultas Teknik, 2023)
PT HMG is an injection molding company that is a subcontractor of PT Ichikoh Indonesia. The variety of product types produced and the irregular placement of products belonging to subcontractors PT Ichikoh Indonesia resulted in a buildup of products, which resulted in ineffectiveness in searching for goods and moving goods. This problem can result in longer handling times and longer handling distances. Based on these problems, PT HMG decided to add a storage area as a warehouse, which will function as a place to store products belonging to subcontractor PT Ichikoh Indonesia. So, it is necessary to design a layout so the products are neatly arranged and make it easier for warehouse operators to search and handle them using dedicated storage and class-based storage methods. The distance obtained using the dedicated storage method was 9,013 m, and the handling time was 180,277 minutes. Meanwhile, using the class-based storage method, the transfer distance was 10,180 m, and the handling time was 203,601 minutes. The selected warehouse layout design is a layout with a dedicated storage method.